Lipid modulators during in vitro maturation of porcine oocytes - Braga, José Victor Cardoso (2020)
Swine in vitro embryo production (IVP) has limitations for better outcomes in reproductive biotechnologies. Among factors impairing IVP, high lipid content in both oocytes and embryos, insufficient media composition and consequent reactive oxygen species (ROS) production are the most prominent. The 1 st paper of this dissertation contains a review regarding metabolizers included into the IVP system in order to sustain nuclear and cytoplasmic maturation, as well as improvement of lipid droplet (LD) consumption. The 2 nd paper reports a study where 50µM DHA was added during the maturation period, with and without porcine follicular fluid (pFF) supplementation. The results demonstrated that DHA without pFF impairs maturation and embryo development. Also, there was no reduction of the lipid content in oocytes treated with DHA, a finding that might be related to metabolic disorders in the cumulus-oocyte complexes (COC). During maturation period, porcine oocytes prefer glucose as substrate for energy consumption. Phenazine Ethosulfate (PES) is an electron receptor that converts NADPH to NADP, inducing glucose utilization through the pentose phosphate pathway (PPP), influencing lipid droplets (LD) metabolism. Forskolin (FSK) is another chemical modulator that stimulates lipolysis through cAMP activation, being also able to synchronize cytoplasmic and nuclear maturation of oocytes. In the 3 rd paper, two concentrations of PES (0.5µM and 0.05µM) and one of FSK (10 µM) were used during the entire in vitro maturation period, for two different experiments. In Experiment 1, oocyte maturation and lipid content were evaluated; and embryo development, embryo cell count and lipid content of blastocysts on day 7 were evaluated in Experiment 2. The concentration of 0.5µM of PES had a negative impact on most of the evaluated parameters, while the lowest PES dose was similar to the negative control (NC) and FSK control in both data of Experiment 1, but also had lower cleavage rates when compared to NC in Experiment 2. Taken together, our results demonstrated impairment of embryo development due to possible disharmony on oocyte maturation and metabolism disorder caused by either addition of DHA or PES. Also, FSK did not improve maturation rates or reduced lipid content.